Bilateral scleritis and sclerokeratitis associated with IgA nephropathy - Garza-Leon, Manuel (Springer-Verlag, 2012)
PURPOSE: The purpose of this study is to report a case of bilateral nodular scleritis in a patient with final diagnosis of IgA nephropathy. METHODS: This is an observational case report. RESULTS: A male patient, 42 years old, presented with a bilateral nodular scleritis and OD sclerokeratitis. He had a previous history of acute otitis media and developed posterior renal failure and arterial hypertension. Clinical and systemic findings suggest Wegener's granulomatosis. A kidney biopsy was performed, and immunoflourescence findings demonstrated granular deposits of IgA in a mesangial pattern confirming the diagnosis of IgA nephropathy CONCLUSIONS: IgA nephropathy should be a differential diagnosis in patients with scleritis and nephropathy.